Pelatihan Pembelajaran Berbasis Teks Secara Digital Dalam Kerangka Penerapan Kurikulum Merdeka - Ragawanti, Debora Tri; Kurniawan, Daniel; Januardi, Josephine (LPPM UMRI, 2024)
Text-based teaching (TBT) has characterized and been emphasized in our national curriculum at elementary and secondary levels. As a consequence, English teaching is based on the TBT principles. Along with the vast development of technology, the implementation of TBT is also integrated with the use of digital technology that is to increase the quality of teaching and learning and to increase students’ technology literacy. This paper reports a workshop on digital TBT in the implementation of “Kurikulum Merdeka.” The objective is to find out teachers’ implementation of digital TBT for teaching English using “Kurikulum Merdeka.” The participants were 26 English teachers under Musyawarah Guru Mata Pelajaran (MGMP) Bahasa Inggris (an English Teachers Forum), Salatiga, Central Java. The methods used in this program were reflective practice and Focus Group Discussion (FGD). The findings revealed that most teachers used all the steps of the TBT cycle. All teachers applied Modelling of Text (MOT), but only a few applied Joint Construction of Text (JCOT). The findings on the use of technology for the TBT cycle demonstrated that the teachers used digital technology more in Building Knowledge of the Fields (BKOF) and Independent Construction of Text (ICOT).